2000
DOI: 10.1007/s11746-000-0162-x
|View full text |Cite
|
Sign up to set email alerts
|

Site‐directed mutagenesis of a highly active Staphylococcus epidermidis lipase fragment identifies residues essential for catalysis

Abstract: A fragment of Staphylococcus epidermidis lipase gene (Lys-303 to Lys-688) was inserted into plasmid pET-20b(+). The resulting C-terminal His-tagged recombinant protein (43 kDa) was overexpressed in Escherichia coli BL21(DE3) as a highly active lipase and was purified with nickel-coupled resin. Putative catalytic sites were determined by site-directed mutagenesis. Mutant enzymes (S418C and H648K) lost enzyme activities, which strongly suggests that the proposed residues of Ser-418 and His-648 are involved in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…The S. epidermidis lipase gene has been subjected to increased lipase activity and improved substrate specificity by site-directed mutagenesis. In comparison with wild-type enzyme, the mutants (M419A and V649I) showed a 2.0 and 4.0-fold increase in the catalytic efficiency (k cat /K m ), respectively (15). In the present work, we found that both the wild-type and mutant lipases (M419A and V649I) could efficiently synthesize various flavor esters in aqueous media.…”
Section: Introductionsupporting
confidence: 46%
“…The S. epidermidis lipase gene has been subjected to increased lipase activity and improved substrate specificity by site-directed mutagenesis. In comparison with wild-type enzyme, the mutants (M419A and V649I) showed a 2.0 and 4.0-fold increase in the catalytic efficiency (k cat /K m ), respectively (15). In the present work, we found that both the wild-type and mutant lipases (M419A and V649I) could efficiently synthesize various flavor esters in aqueous media.…”
Section: Introductionsupporting
confidence: 46%
“…A lipase from S. saprophytics presented a K m value of 1.47 mM for the same substrate [31] and a recombinant lipase from S. epidermidis presented 0.9 mM [37]. The k cat value presented by the recombinant lipase from S. xylosus (0.0078 s -1 ) was lower than recombinant lipase of S. epidermidis (25.1 s -1 ) [37] as well as catalytic efficiency (0.0154 and 28.2 s -1 mM -1 , respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Three pH values (7.0, 8.0, and 9.0) and three temperatures (25,37, and 42°C) were tested with pNPC 4 as substrate in order to determine the pH and temperature dependence on the activity of recombinant S. xylosus lipase (Fig. 4).…”
Section: Effect Of Ph and Temperature On Lipase Activitymentioning
confidence: 99%
“…The GehC gene was first cloned and characterized by Farrell et al (1993). Structure-function studies of GehC have shown that aminoacid residues Met419 and Val649, which follow the catalytic triad, affect substrate specificity and catalytic efficiency, and that Ser418 is the active site (Chang et al, 2000). GehC exhibits a higher esterification yield with medium-chain fatty acids (from C8 to C14), with an optimal yield for lauric acid (Chang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal regions of these proteins are closely related: 49% of the 386 residues are identical and 60% of the differences reflect conservative changes. The significant differences in substrate specificity and enzyme catalytic efficiency between these two enzymes suggest that dissimilar amino-acid residues, particularly around the active site, are important for their biochemical properties (Chang et al, 2000). To clarify the mechanism by which rGehC catalyzes esterification in aqueous solvents, rGehC was crystallized and modelled using ShLip (PDB entry 2hih) as the initial model.…”
Section: Introductionmentioning
confidence: 99%